Peningkatan Hasil Belajar Peserta Didik Melalui Pembelajaran Problem Based Learning (PBL) pada Materi Gereja sebagai Tanda dan Sarana Keselamatan - Helena Br Karo Sekali (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to improve student learning outcomes through the application of Problem-Based Learning (PBL) in Catholic Religious Education, especially in the material "The Church as a Sign and Means of Salvation". Using a classroom action research approach, this study was conducted in two cycles with 18 grade VIII students at SMP NEGERI 1 PABULUAN during the 2024/2025 school year. Data is collected through observation, tests, questionnaires, and documentation. The results showed that the implementation of PBL increased student engagement, with 70% of students actively participating in discussions and 65% showing improved critical thinking skills. The average test score increased from 65 in the initial condition to 72.5 in the first cycle, with 65% of students achieving the minimum completeness criteria. Character development in terms of Caring, Confident, and Professional (P3) also shows a positive trend. Although not all success indicators were achieved in the first cycle, significant improvements were observed in several aspects. The study concluded that PBL has the potential to improve student engagement and critical thinking skills in Catholic Religious Education, with recommendations for further optimization in the second cycle.